Leadership Style and Motivation Impact on Employee Performance at The Faculty of Economics University of Sultan Ageng Tirtayasa - Siti Epa Hardiyanti (PT Larva Wijaya Penerbit, 2022)
This study aims to determine the effect of leadership style and motivation on employee performance at the Faculty of Economics, University of Sultan Ageng Tirtayasa. The sample in this study was 40 respondents who were taken in 2013 from the population census employee of the Faculty of Economics, Sultan Ageng Tirtayasa University. The method of analysis used in this study is the method of multiple linear regression analysis by testing for partial test and simultaneous test (F-test and t-test). The results showed that simultaneously there is a significant influence between leadership style and motivation on employee performance at the Faculty of Economics, University of Sultan Ageng Tirtayasa. Then, partially there is a significant influence between leadership style on employee performance, and motivation on employee performance. The meaning that a leader in improving the performance of his employees must pay attention to the level of motivation and leadership style provided by him.